Effects of being uninsured or underinsured and living in extremely poor neighborhoods on colon cancer care and survival in California: historical cohort analysis, 1996-2011 - Gorey Kevin M; Luginaah Isaac N; Holowaty Eric J; Zou Guangyong; Hamm Caroline; Bartfay Emma; Kanjeekal Sindu M; Balagurusamy Madhan K; Haji-Jama Sundus; Wright Frances C (BMC, 2012)
Abstract Background We examined the mediating effects of health insurance on poverty-colon cancer care and survival relationships and the moderating effects of poverty on health insurance-colon cancer care and survival relationships among women and men in California. Methods We analyzed registry data for 3,291 women and 3,009 men diagnosed with colon cancer between 1996 and 2000 and followed until 2011 on lymph node investigation, stage at diagnosis, surgery, chemotherapy, wait times and survival. We obtained socioeconomic data for individual residences from the 2000 census to categorize the following neighborhoods: high poverty (30% or more poor), middle poverty (5-29% poor) and low poverty (less than 5% poor). Primary health insurers were Medicaid, Medicare, private or none. Results Evidence of mediation was observed for women, but not for men. For women, the apparent effect of poverty disappeared in the presence of payer, and the effects of all forms of health insurance seemed strengthened. All were advantaged on 6-year survival compared to the uninsured: Medicaid (RR = 1.83), Medicare (RR = 1.92) and private (RR = 1.83). Evidence of moderation was also only observed for women. The effects of all forms of health insurance were stronger for women in low poverty neighborhoods: Medicaid (RR = 2.90), Medicare (RR = 2.91) and private (RR = 2.60). For men, only main effects of poverty and payers were observed, the advantaging effect of private insurance being largest. Across colon cancer care processes, Medicare seemed most instrumental for women, private payers for men. Conclusions Health insurance substantially mediates the quality of colon cancer care and poverty seems to make the effects of being uninsured or underinsured even worse, especially among women in the United States. These findings are consistent with the theory that more facilitative social and economic capital is available in more affluent neighborhoods, where women with colon cancer may be better able to absorb the indirect and direct, but uncovered, costs of care.